The Effect of Synthetic Structural Analytical Method on Beginning Reading Ability of Students in Makassar City - Umar Sulaiman; Andi Hasrianti (Ethical Lingua: Journal of Language Teaching and Literature, 2021)
This study aims to see the effect of the application of the Structural Analytical Synthetic (SAS) method on the students' initial reading ability. This research is quasi-experimental research using the “Posttest-Only Control Group Design” design. The population in this study were all students of class II SDN in Makassar City, which consisted of 314 schools with a total of 13,188 students. Sampling used the solving formula and proportional random sampling technique so that the research sample was obtained, namely class IIA1 SD Rappocini Makassar as a control class with a total of 30 students and class IIA2 SD BTN Makassar local government as an experimental class with a total of 30 students. The data obtained were analyzed with descriptive statistics and inferential statistics. The results of descriptive statistical analysis show that the students' initial reading ability using the Structural Analytical Synthetic (SAS) method the average value obtained is 81.90, with a maximum value of 100 and a minimum of 68.33 and these results are in very good category, while Student learning outcomes using conventional methods the average value obtained is 55. 61, with a maximum value of 80 and a minimum of 47.5, and these results are in the medium category. The results of inferential statistical testing with Independent Samples T-Test obtained a significance value of p = 0.001 < = 0.05. This means that H0 is rejected and HI is accepted, thus the application of the Structural Analytical Synthetic (SAS) method has an effect on the early reading ability of SDN students in Makassar City.